Liver abscess in children: challenges in management - Chaubey, Digamber; Pandey, Anand; Kumar, Piyush; Gupta, Archika; Rawat, Jiledar; Wakhlu, Ashish; Kureel, Shiv Narain (International Surgery Journal, 2016)
Background:Liver abscess (LA) is an important cause of morbidity in children. It is more common in developing countries than the developed world. Since it is common in India, we have tried to evaluate the clinical profile of pediatric liver abscess and management protocol. Methods: This was a retrospective, observational, cohort study. The duration was from February 2011 to August 2016. All the patients with liver abscess were included in it. The patients were evaluated for their complaints, possible predisposing factors, mode of diagnosis, interventions, if any, and duration of stay. Intervention was made according to the ultrasonography abdomen and the number and amount of abscess cavities. Results:There were 32 patients. The mean age of patients was 5.52 years. The clinical features were fever (25, 78%), pain in right hypochondrium (19, 59%), abdominal distension (4, 12.5%), subacute intestinal obstruction (2, 6.25%), and peritonitis (2, 6.25%). Rupture of abscess was noted in three patients. Conservative management was successful in three patients. USG guided needle aspiration was successful in 5 patients. Pigtail insertion was needed in 21 patients. Laparotomy was performed in three patients. One patient with severe sepsis and coagulopathy expired. All other patients were discharged. Conclusions:LA is an important cause for morbidity in children. If not taken care of, it may lead to rupture and mortality. High index of suspicion, early screening, and appropriate intervention in form tailored management may fetch good results.